Anaesthesia, Pain, Intensive Care and Emergency Medicine — A.P.I.C.E. Proceedings of the 16th Postgraduate Course in Critical Care Medicine Trieste, Italy — November 16–20, 2001 - Gullo, Antonino (Springer Milan, 2002)
Basic research, progress in technology and informatics, and the success of clinical pharmacology are the fundamental bases of this interesting field of medicine. Nowadays, critical care medicine is no longer for experts only, but it is a field in which researchers and clinicians, nurses and technical staff work in an interdisciplinary way, each offering their own skills. The volume is divided in six sections, devoted to critical care key issues, to lung diseases, to trauma, to acid-base equilibrium, to perioperative medicine, and to obstetrics
Keywords: Anesthesiology; Intensive / Critical Care Medicine; Critical care medicine; Intensivtherapie; Schmerztherapie; Notfalltherapie; Anästhesie; Konferenzschrift -- 2001 -- Triest